The Oral Cavity: A Study of the Development, Anatomy and Histology of the Oral Cavity - Jessica Parker; Lisa Lee (Association of American Medical Colleges, 2011)
Abstract This is a concise, yet comprehensive review of the oral cavity intended for dental students, medical students, and residents who are preparing for the board examinations. The cogent 20-minute narrated tutorial, and accompanying PowerPoint slides describes embryonic development and the maturation of the oral cavity into structures of the adult oral cavity, providing a full review of the oral cavity development, anatomy, and histology. An anatomical review of the oral cavity is followed by a detailed histological review of the structures of the oral cavity. The presentation maybe used in private or in the lecture hall as it has been designed with the new generation of students' learning preferences in mind: concise dissemination of knowledge in a format that is conducive to anytime, anywhere learning. Original images provided in the presentation may be adapted for use in a variety of educational settings to increase discussion and foster a comprehensive review.